PENDUGAAN DAYA PRODUKSI SUSU DAN BEBERAPA NILAI PARAMETER GENETIK PADA SAPI PERAH FRIES HOLLAND - Neli Definiati; Sartini Sartini (Jurnal Peternakan Indonesia (Indonesian Journal of Animal Science), 2006)
The aims of the present research were to calculate some genetically parameters for estimation of milk production potency of dairy cattle based on the recorded data for 10 years of production. Parameter calculated included: heredity, repeatability and production capacity. The data was collected from PT. Taurus Dairy Farm Sukabumi during the period of 1990-2000. Heredity and repeatability values were determined by variance and covariance analysis based on paternal half in completely randomized design. Calculation of milk production capacity was based on most probable producing ability (MPPA) formula. Results showed that the highest milk production of about 3.565.71  670.021 kg/y was obtained during the first lactation period and followed by the fourth lactation period of 3.331,80  806,35 kg/y. The highest heredity value of 0,36  0,35 was obtained at first lactation, followed by third lactation of 0,25  0,31, fourth lactation 0,22  0,30. The repeatability value of milk production was found 0, 33.